Einflüsse zur Klärung und Prognose der Wohnbauflächenneuinanspruchnahme. - Iwanow, Irene; Gutting, Robin; Stutzriemer, Sylke (Taylor & Francis, 2015)
For a more sustainable management of residential building land, a deeper understanding of the underlying driving forces on a small scale is required. The aim of this paper is therefore to present a systematization of the driving forces of usage and acquisition of undeveloped residential building land, which applies a structure to the known factors, groups them and in particular shows the relationships between them. In order to achieve this it is necessary to look at the current discussion, which presents existing qualitative and quantitative approaches. Qualitative approaches display deficits especiallv in terms of the logical organization of influencing factors. Quantitative approaches, however, usually desregard theoretical discussion.
Keywords: Wohnungswesen; Wohnungsbau; Wohnfläche; Flächennutzung; Wohnbaufläche; Raumentwicklung; Raumplanung; Flächennutzungsplanung; Bodennutzung; Flächenmanagement